Migraine-Related Vertigo and Somatoform Vertigo Frequently Occur in Children and Are Often Associated - Langhagen, Thyra; Schroeder, A. Sebastian; Rettinger, Nicole; Borggraefe, Ingo; Jahn, Klaus (Neuropediatrics, 2013)
Migraine-related syndromes are a common cause of episodic vertigo and dizziness in children. Somatoform vertigo (SV) is an important cause of chronic dizziness, especially in adolescents. Our aim was to elucidate the comorbidity of migraine and SV. Three diagnostic groups were defined: migraine-related vertigo (MRV), SV, and combined migraine-related and SV (MSV). A retrospective analysis was performed on patient data (demographics, diagnosis, neuro-orthoptic and neurologic status, and results of vestibular and balance testing) from 168 patients who were presented to the German Center for Vertigo and Balance Disorders (IFB) over a 2.5-year period. Mean age of patients was 12 ± 4 years (range: 1.4 to 18 years). The most frequent diagnosis was MRV (28%), followed by MSV (19%) and SV (14%). MSV occurred most frequently in adolescent girls (25%). MRV was the most common cause of dizziness in our cohort. MSV ranked second overall but ranked first in adolescent girls, followed by isolated SV. SV was most prevalent in adolescent girls. MRV, MSV, and SV account for about 60% of diagnoses established in our tertiary referral center. Competent care of childhood migraine should include skill in detecting both the clinical symptoms of vertigo and overlapping somatoform symptoms.
Keywords: migraine-related vertigo; somatoform vertigo; benign paroxysmal vertigo in childhood